The SP-ET index is a new index for assessing the vertical position of patella - Jia Li; Mao Yuan; Lanyu Qiu; Bo Sheng; Fan Yu; Haitao Yang; Furong Lv; Fajin Lv; Wei Huang (Insights into Imaging, 2022)
Abstract Background Some parameters in previous studies did not better reflect the vertical position of the patella relative to the femoral trochlear. This study aimed to assess the value of the most superior point of patella-entrance of femoral trochlea distance ratio (SP-ET index) as a newer index in defining the vertical position of patella relative to the trochlea, correlate it with the Insall–Salvati ratio, and investigate the effect of the new index on patellar cartilage lesions. Methods A total of 99 knees of 77 patients with patellar cartilage lesions were retrospectively analyzed using magnetic resonance imaging (MRI) data. The Insall–Salvati ratio and SP-ET index were measured on MR images. Ninety-nine knees just with meniscus rupture were enrolled as the control group. The two parameters of the patellar cartilage lesions were compared with those of the control group. Results The Insall–Salvati ratio and SP-ET index in the patellar cartilage lesions group were significantly higher than those in the control group (p < 0.001). The SP-ET index showed a moderate positive correlation with the Insall–Salvati ratio (r = 0.307, p < 0.001). Receiver operating characteristic (ROC) analysis showed that the diagnostic efficiency of the SP-ET index was better than that of the Insall–Salvati ratio in patients with patellar cartilage lesions. Conclusion The SP-ET index may be a useful complement parameter to define the vertical position of the patella relative to the femoral trochlear. Increased SP-ET index may be an important risk factor for patellar cartilage lesions.